Scanning tunneling microscopy investigations of the ordered thin films of squaraine dye molecules on HOPG - Stawasz, Michele E., author; Parkinson, Bruce, advisor; Van Orden, Alan, committee member; Levinger, Nancy, committee member; Dorhout, Peter, committee member; Field, Stuart, committee member (Colorado State University. Libraries, 2002)
Squaraines are organic dye molecules with a symmetrical donor-acceptor-donor (DAD) structure that allows them to undergo intra- and intermolecular donor-acceptor charge transfer. These donor-acceptor interactions drive squaraines to form ordered aggregates in both solution and in the solid state. In addition squaraines absorb very strongly in the red region of the visible spectrum. As a result of these characteristics, squaraines are used in industry as thin film photoconductors in laser printers and photocopiers. The orientation and aggregate state of the molecules within these films has been shown to effect device efficiency. Furthermore, the orientation of molecules at the film-substrate interface has been known to affect the order of the rest of the film. Thus, the interfacial ordering of squaraines is of importance to efficient device design.

This Dissertation describes the use of scanning tunneling microscopy (STM) to investigate the adsorption and 2D ordering of ultrathin films of squaraines deposited from phenyloctane solution onto the (0001) surface of highly oriented pyrolytic graphite (HOPG). A total of 11 squaraine molecules, varying in their dialkylamino tail length (CH3 to C18H37), symmetry (equal or unequal tail length), and phenyl ring substituent (OH or H), were investigated. We found that, regardless of structural variation, squaraines are highly surface active, forming monolayer and multiple layer structures (up to four layers) consisting of ordered domains (tens of nm to microns in diameter). Two general types of aggregate structure were observed, herringbone and row, although many polymorphs of these two types were observed (oftentimes for a single molecule). Shorter-tailed squaraines tended to exhibit herringbone structures whereas only row structures were exhibited by longer-tailed squaraines. Determination of the type of structure exhibited appeared to depend upon a delicate balance of chromophore-chromophore DA interactions, tail-tail interactions, and tail-HOPG interaction. It was found that hydroxylated and non-hydroxylated molecules exhibited the same structures, suggesting that intermolecular hydrogen bonding was not a factor in the determination of adsorbate aggregate structure. Changing the symmetry, by employing different tail lengths within the same molecule, showed that the adsorbate structure was determined by the longer of the tails, with the shorter tails providing little or no influence. Interaction of the tails with the HOPG caused squaraines with longer tail lengths (≥ 12 carbons) to exhibit an orientational relationship to the HOPG lattice whereas shorter-tailed squaraines showed no distinct relationship to the HOPG lattice.
Keywords: analytical chemistry